A REVIEW: FACILE AND GREEN SYNTHESIS OF MARINE MACROALGAE AND ITS PHOTOCATALYTIC PERFORMANCE ON POLLUTED WATER REMEDIATION - ., Ramadhani; Said, Ahmad (Journal of Aquatropica Asia, 2024)
This review critically examines the burgeoning field of research focused on the environmentally benign synthesis of metallic nanoparticles exploiting the unique properties and diverse array of marine macroalgae species. Harnessing macroalgal biomolecules as reductants and stabilizers, numerous findings have discovered the biosynthesis of silver, gold, iron oxide, zinc oxide, and other nanoparticles through a sustainable "phycosynthesis" technique without toxic chemicals. Extensively characterized for their morphologies and properties, these algae-mediated nanoparticles exhibit notable photocatalytic activities in degrading various organic dyes and pollutants. Particularly, over 90% degradation efficiency has been achieved for dyes like methylene blue, methyl orange, and rhodamine B utilizing nanoparticles produced from macroalgae such as Sargassum horneri, Syringodium isoetifolium and Ulva lactuca. The mechanism is hypothesized to involve photoexcitation generating reactive oxidative species on the nanoparticle surface that rapidly cleave dye molecules. Improved understanding of the roles of macroalgal biomolecules and optimization of synthesis conditions may enable enhanced catalytic performances. With their widespread availability and biodiversity remaining largely untapped, marine macroalgae prove promising as renewable resources for developing eco-friendly water remediation technologies through metal/metal oxide nanocatalyst design.